2015
DOI: 10.1016/j.drugalcdep.2015.06.018
|View full text |Cite
|
Sign up to set email alerts
|

Acute oral administration of the novel, competitive and selective glucocorticoid receptor antagonist ORG 34517 reduces the severity of ethanol withdrawal and related hypothalamic–pituitary–adrenal axis activation

Abstract: Background The development of ethanol dependence is associated with alterations in hypothalamic-pituitary-adrenal (HPA) axis and activation of type II glucocorticoid receptors (GR). These effects may contribute to withdrawal-associated anxiety, craving and relapse to drinking. The present studies examined acute and oral administration of the novel, selective and competitive GR antagonist ORG 34517 on the severity of ethanol withdrawal. Methods Adult, male Sprague-Dawley rats were administered ethanol (4g/kg/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 36 publications
1
16
0
Order By: Relevance
“…Given that nasogastric gavage administration of MPEP (10 mg/kg) for one month reduced Parkinsonian symptoms in non-human primates (Morin et al, 2013), we chose to deliver this compound to subjects orally suspended in either ethanol-containing or an isocaloric diet. Ethanol and control diets were composed of 30% v/v Vanilla Ensure® (Abbott Nutrition, Columbus Ohio) and an equal quantity of double-distilled water (after Sharrett-Field et al, 2013; Reynolds et al, 2015B). Ethanol-containing diets were composed of 40% v/v 200 proof ethanol (Sigma-Aldrich, San Diego, CA) whereas control diets were isocalorically matched to ethanol-containing diets via substitution of maltose (Sigma-Aldrich) so as to yield equivalent caloric intake.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Given that nasogastric gavage administration of MPEP (10 mg/kg) for one month reduced Parkinsonian symptoms in non-human primates (Morin et al, 2013), we chose to deliver this compound to subjects orally suspended in either ethanol-containing or an isocaloric diet. Ethanol and control diets were composed of 30% v/v Vanilla Ensure® (Abbott Nutrition, Columbus Ohio) and an equal quantity of double-distilled water (after Sharrett-Field et al, 2013; Reynolds et al, 2015B). Ethanol-containing diets were composed of 40% v/v 200 proof ethanol (Sigma-Aldrich, San Diego, CA) whereas control diets were isocalorically matched to ethanol-containing diets via substitution of maltose (Sigma-Aldrich) so as to yield equivalent caloric intake.…”
Section: Methodsmentioning
confidence: 99%
“…Withdrawal behavior was monitored in a square Plexiglas chamber for two minutes. During this time, two experimenters, blinded to experimental conditions, rated physical effects of withdrawal using a modified behavioral scale that was described in detail previously in our laboratory (Reynolds et al, 2015B; Self et al, 2009) using a 10-point discrete scale (i.e., all or nothing). This scale measured the following behaviors: rigidity, tremor, stereotypy, retropulsion, dystonic gait, hypoactivity, aggression, splayed paws, vocalization, and seizure.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Numerous in vivo studies have demonstrated enhanced striatal dopamine and glutamate efflux in animals exposed to stressors and methamphetamine (Matuszewich and Yamamoto, 2004) and research has indicated that exposure to chronic CORT significantly enhanced methamphetamine-induced dopaminergic nerve terminal damage (Kelly et al, 2012). Others have demonstrated the importance of the GR in the development of ethanol dependence and subsequent ethanol withdrawal (Jacquot et al, 2008; Reynolds et al, 2015; Rotter et al, 2012; Sharrett-Field et al, 2013). Taken together, these findings demonstrate the ability of stress and the resulting rise in CORT levels to sensitize the reward pathway, and in particular the VTA, to future excitatory amino acid signaling such as that seen with psychostimulant and ethanol use.…”
Section: Discussionmentioning
confidence: 99%